2006
DOI: 10.2174/156802606777303658
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Structural Diversity of siRNA Molecules

Abstract: Short interfering RNAs (siRNAs) are 21-23 nt long double-stranded oligoribonucleotides which in mammalian cells exhibit a potency for sequence-specific gene silencing via an RNA interference (RNAi) pathway. It has been already proven that exogenous, chemically synthesized siRNA molecules are effective inhibitors of gene expression and are widely applied for analysis of protein function and proteomics-based target identification. Moreover, since their discovery siRNA molecules have been implemented as potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 91 publications
0
36
0
Order By: Relevance
“…This modification pattern was most uniformly active when a single strand was modified, and ASm was used for most of the studies reported herein. Given the extent to which functional performance of chemically modified siRNAs and DsiRNAs varies with sequence context, we would not be surprised if nuclease resistance without compromising potency of the RNA duplex as a trigger of RNAi (Nawrot and Sipa, 2006;Zhang et al, 2006). Modification of a few residues is usually well tolerated; however, widespread modification of the siRNA can lead to reduced activity compared to unmodified RNA.…”
Section: Discussionmentioning
confidence: 99%
“…This modification pattern was most uniformly active when a single strand was modified, and ASm was used for most of the studies reported herein. Given the extent to which functional performance of chemically modified siRNAs and DsiRNAs varies with sequence context, we would not be surprised if nuclease resistance without compromising potency of the RNA duplex as a trigger of RNAi (Nawrot and Sipa, 2006;Zhang et al, 2006). Modification of a few residues is usually well tolerated; however, widespread modification of the siRNA can lead to reduced activity compared to unmodified RNA.…”
Section: Discussionmentioning
confidence: 99%
“…While chemical modifications of siRNAs and Dicersubstrate RNAs have been extensively studied (Nawrot and Sipa 2006;Zhang et al 2006;Collingwood et al 2008;Robbins et al 2009), synthetic sshRNAs have not been similarly studied. Because of their different structures and probable differences in how they are processed by the RNAi machinery, modifications that have proven effective for siRNAs or Dicer-substrate RNAs may not necessarily be effective with sshRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to reach this goal is the introduction of chemical modifications into siRNA duplexes (Manoharan 2004;Fougerolles et al 2005;Uprichard 2005;Nawrot and Sipa 2006). Research efforts in this field are focused on improving three of the most important siRNAs features: (1) cell membrane permeability, (2) in vivo stability, and (3) specificity of their silencing action.…”
Section: Introductionmentioning
confidence: 99%